PUBLICATION OF THE ACCOUNTING POLICIES IN ACCORDANCE WITH IAS 8 - Bešlić, Ivana; Bešlić, Dragana (International Journal of Economic Practice and Policy, 2013)
In global economy, accounting policies respectively the notes to financial statements of the enterprise are used as a complement for good quality financial reporting and strategic management. Selected accounting policies aligned with IAS/IFRS, as a key element of the notes complement content of accounting information in financial statements: balance sheet, income statement, cash flow statement, statement of changes on capital. This paper focuses on: 1. accounting principles and standards as well as origination in accounting policies, 2. choice of accounting policies in the area of long-term assets and inventory, 3. important features of notes to financial statements. In the Republic of Serbia publication of accounting policies must be in accordance with IAS 8. In this paper the autors used following methods of research: an overview relevant literature, the method of analysis, the method of synthesis, the method of induction, method of deduction and mathematical method.